2018
DOI: 10.1016/j.jastp.2018.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Sausage oscillations in a plasma cylinder with a surface current

Abstract: The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. Please see the 'permanent WRAP url' above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Let us name only one possible equilibrium configuration where essentially the only difference from ER83 is the introduction of a magnetically twisted boundary layer. Radial fundamental FSMs may be trapped regardless of the axial wavenumber (e.g., Khongorova et al 2012;Lim et al 2018), the corresponding eigenfunctions possessing spatial scales that do not far exceed the cylinder radius (e.g., Mikhalyaev & Bembitov 2014;Lopin 2021). One readily deduces that these radial fundamental FSMs may indeed show up in reality, even though a definitive answer relies on a detailed study from the IVP perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Let us name only one possible equilibrium configuration where essentially the only difference from ER83 is the introduction of a magnetically twisted boundary layer. Radial fundamental FSMs may be trapped regardless of the axial wavenumber (e.g., Khongorova et al 2012;Lim et al 2018), the corresponding eigenfunctions possessing spatial scales that do not far exceed the cylinder radius (e.g., Mikhalyaev & Bembitov 2014;Lopin 2021). One readily deduces that these radial fundamental FSMs may indeed show up in reality, even though a definitive answer relies on a detailed study from the IVP perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Introducing magnetic twist in the cylindrical geometry (r, θ, z), namely allowing the equilibrium magnetic field B 0 to possess an azimuthal component, is one possibility. This twist may be introduced in the interior (e.g., Erdélyi and Fedun 2007), the exterior (e.g., Lim et al 2018;Lopin and Nagorny 2019b), an annulus between the two (e.g., Khongorova et al 2012), or throughout the equilibrium (e.g., Giagkiozis et al 2015Giagkiozis et al , 2016. If the ER83 equilibrium is modified only by revising B 0 in the interior such that its θ-component B 0θ (r) ∝ r, then Erdélyi and Fedun (2007) showed that the dispersive properties of trapped FSMs are hardly affected even when the maximum of B 0θ reaches 20% of the axial magnetic field strength (B 0z ) at the loop axis (Figure 10 therein).…”
Section: Coronal Loops With Magnetic Twistmentioning
confidence: 99%